Performance driven culture in the public sector: The case of Nordic countries - Michaela Kotková Stříteská; Yee Yee Sein (Administrative Sciences, 2021)
Public sector organizations face a lack of efficiency and ineffectiveness in providing their mandates due to fear of change among the public service workers. Public sector managers can instill a high performance-driven culture in employees of the public sector. For this reason, the study aims to define a set of key characteristics of organizational culture that contribute to effective performance measurement and management of public sector organizations. The qualitative research method is employed in this paper using case study comparative analysis. To get the objectives of the study, selected local governments from three different Nordic countries are analyzed. As discovered from the case study analysis, these local governments have successfully constructed and implemented performance measurement and management systems. Concurrently, they practice performance-driven culture key characteristics to achieve their organizational targets without any significant difficulties. Three key characteristics (strong performance-driven leadership, report and communicate performance, review and discuss performance) are used in all selected local governments, and one (the reward system) is missing. All four key characteristics are employed only in Helsinki, which is a benchmark for other local governments. This study's results can thus serve as an example of best practice for other public sector organizations within Europe.
Keywords: 350; organizational culture; performance driven culture; local government; performance measurement; management system